2023
DOI: 10.12911/22998993/168349
|View full text |Cite
|
Sign up to set email alerts
|

The Meteorological Conditions of Precipitation Deficits in the Cultivation of Winter Wheat in Central and Eastern Poland

Abstract: The problem of precipitation deficits constitutes an issue that is significant on a global, regional, and local scale, particularly in the aspect of climate warming. The purpose of this research was to determine the amount, frequency and trends of precipitation deficits in the cultivation of winter wheat in central and eastern Poland, over a period of fifty years . This study used the values of average monthly air temperatures, as well as monthly total precipitation, decadal precipitation needs of winter wheat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Adding green light to red and blue light may increase chlorophyll content, photosynthesis, and production of smaller-sized tubers. A high proportion of red and blue light may increase tuber production, while adding green light may favor the production of smaller-sized tubers [55][56][57]. In summary, our research has shown the significant impact of potato varieties on yield and its quantitative characteristics.…”
Section: The Impact Of Varieties On Yield and Its Quantitative Charac...mentioning
confidence: 67%
See 3 more Smart Citations
“…Adding green light to red and blue light may increase chlorophyll content, photosynthesis, and production of smaller-sized tubers. A high proportion of red and blue light may increase tuber production, while adding green light may favor the production of smaller-sized tubers [55][56][57]. In summary, our research has shown the significant impact of potato varieties on yield and its quantitative characteristics.…”
Section: The Impact Of Varieties On Yield and Its Quantitative Charac...mentioning
confidence: 67%
“…Studies by Skowera et al [37,57] also indicate spatial and temporal differences in rainfall deficits during potato cultivation in Poland. The highest risk of rainfall deficit, according to them, occurs in June, which is unfavorable for potatoes, as potato plants are then in the tuberization phase and forming new tubers.…”
Section: The Influence Of Environmental Conditions On Yield and Its S...mentioning
confidence: 94%
See 2 more Smart Citations
“…Additionally, the interaction between the tested factors and specific experimental years can further contribute to the variability of results in subsequent seasons [35,36]. Skowera et al [37] have shown that in Poland, the highest risk of rainfall shortage occurs in June, a critical period as winter wheat enters the grain-filling stage from mid-June. Xu et al [29] have reported that air temperatures play an important role in the proper growth and development of field crops, and their unfavorable patterns can be just as detrimental as a lack of precipitation.…”
Section: Resultsmentioning
confidence: 99%